ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MOBIL MITSUBISHI XPANDER PADA PT BATAVIA BINTANG BERLIAN CIPONDOH KOTA TANGERANG - Albiansyah, Albiansyah; Salsyadila, Salsyadila (Management Research and Business Journal, 2023)
ABSTRACT This study aims to determine the effect analysis of price, product quality and brand image on consumer purchasing decisions for Mitsubishi Xpander cars at PT Batavia Bintang Berlian Cipondoh, Tangerang City, either partially or simultaneously (together). This study uses primary data in the form of a sample of 50 Mitsubishi Xpander car consumers at PT Batavia Bintang Berlian with data collection techniques through distributing questionnaires. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis, coefficient of determination test (R2), partial test (t) and simultaneous test (F). The test results of this study indicate that the multiple regression analysis has the equation Y = 2.774 + 0.275X1 + 0.468X2 + 0.196X3. The test results for the coefficient of determination (R2) have an Adjusted R Square of 0.888 or 88.8%, meaning that the Purchase Decision variable is influenced by price, product quality and brand image variables. While the remaining 11.2% is influenced by other variables outside the research. The results of the partial test (t) show that the price variable (X1) on purchasing decisions (Y) has a tcount value of 2.995 > ttable 2.01290 with a significance level of 0.004 <0.05, product quality variable (X2) on purchasing decisions (Y) has tcount value 5.649 > ttable 2.01290 with a significance level of 0.00 <0.05 and the brand image variable (X3) on purchasing decisions (Y) has a tcount value of 2.462 > ttable 2.01290 with a significance value of 0.018 <0.05. Then the price variable (X1) has a partially significant effect on the purchasing decision variable (Y), the product quality variable (X2) has a partially significant effect on the purchasing decision (Y), and the brand image variable (X3) has a partially significant effect on the purchasing decision ( Y) for Mitsubishi Xpander car consumers. Simultaneous test results (F) show Fcount 130.737 > Ftable 2.81 with a significant level value of 0.000, while Ftable is 2.81 with a significant level of 0.000 <0.05, This means that the hypothesis states that the variables Price (X1), Product Quality (X2 ) and Brand Image (X3) have a significant influence simultaneously (simultaneously) and positively on the Purchase Decision (Y) of PT Batavia Bintang Berlian Cipondoh Tangerang City.